Rectangular Based Pyramids

[highlight] volume = (base area [multiply] height) [divide] 3 [/highlight] [code] Surface area:[br] SA = (v [multiply] x) + (u [multiply] x) + (x [multiply] y) [/code] [table] [tr] [td style='padding:5px;font-size:130%;font-weight:400;']x[/td][td style='padding:5px;text-align:left;']length of base[/td] [/tr] [tr] [td style='padding:5px;font-size:130%;font-weight:400;']y[/td][td style='padding:5px;text-align:left;']width of base[/td] [/tr] [tr] [td style='padding:5px;font-size:130%;font-weight:400;']u[/td][td style='padding:5px;text-align:left;']slanted height on [b]y[/b] side of base[/td] [/tr] [tr] [td style='padding:5px;font-size:130%;font-weight:400;']v[/td][td style='padding:5px;text-align:left;']slanted height on [b]x[/b] side of base[/td] [/tr] [img src='https://res.cloudinary.com/deylrqt2d/image/upload/v1485121597/pyramid_diagram_vehfci.jpg'] To use the previously stated formula, you must actually have the slanted heights, so you must use pythagoras's theorem alongside the labeled lengths [b]t[/b] and [b]w[/b] to get the slanted height.[br] Think of it as taking a cross section of the pyramid, and getting a triangle. The bottom is half of one of the side, you are supplied with the height (or find it out), and then you get either of the slanted heights[br].